Evaluation of apoptotic potential of glyphosate metabolites and impurities in human peripheral blood mononuclear cells (in vitro study). (January 2020) - Kwiatkowska, Marta; Michałowicz, Jaromir; Jarosiewicz, Paweł; Pingot, Daria; Sicińska, Paulina; Huras, Bogumiła; Zakrzewski, Jerzy; Jarosiewicz, Monika; Bukowska, Bożena
Abstract: Glyphosate is used for cereal, vegetable and fruit crops for reducing or inhibiting the growth of weeds as well as a desiccant for various grain crops. That is why, glyphosate has been shown to be accumulated in humans and animals through ingestion of food of both plant and animal origin. The study aimed to assessed the effect of glyphosate, its metabolites: aminomethylphosphonic acid (AMPA), methylphosphonic acid and its impurities: PMIDA, N -methylglyphosate, hydroxymethylphosphonic acid and bis(phosphonomethyl)amine on apoptosis induction in human peripheral blood mononuclear cells (PBMCs). PBMCs were exposed to the compounds studied at the concentrations ranging from 0.01 to 5 mM for 4 h. We have observed an increase in reactive oxygen species (including hydroxyl radical) and cytosolic calcium ions levels as well as reduction of transmembrane mitochondrial potential (ΔΨm) in PBMCs exposed to the compounds examined. All substances studied changed PBMCs membrane permeability, activated caspase-8, -9, -3 and caused chromatin condensation, which showed that they were capable of inducing apoptosis both via extrinsic and particularly intrinsic pathway. Generally the study demonstrated that there were no differences between apoptotic changes induced by glyphosate, its metabolites or impurities, and observed changes were provoked by high concentrations of investigated compounds. Graphical abstract: Image 1 Highlights: Glyphosate metabolites and impurities increased ROS level in PBMCs. The increase in cytosolic calcium ion level and reduction of ΔΨm was noted. The compounds activated caspase-8, -9, -3 and caused chromatin condensation. The compounds only in high concentrations induced apoptosis in PBMCs. Glyphosate its metabolites and impurities exhibited comparable apoptotic potential.